Kältebilder Ästhetik und Erkenntnis am Gefrierpunkt - Bruhn, Matthias (Bildwelten des Wissens, 2021)
Cold has always been of fundamental importance to human culture, but it was not until the industrial age that possibilities of artificial cooling were invented which are taken for granted today. However, colling was also accompanied by new possibilities for gaining knowledge. The frozen movement became a metaphor for technical still life, and without cryogenics, there would be no modern computing and imaging processes. Such possibilities of ice-cold observation are contrasted by losses of visibility, due to frost or precipitation, just as the artificial lowering of temperatures fuels climate change precisely through its energy consumption. Cooling technology is reaching new lows and highs in every respect - with extensive consequences for knowledge and perception.